Uji Silang Digital sebagai Alternatif Uji Banding Manual Pemeriksaan Mikroskopis Malaria di Kulon Progo - Elsa Herdiana Murhandarwati; Anis Fuad; Guntur Budi Herwanto; Rizqiani Amalia Kusumasari; Mahardika Agus Wijayanti; supargiyono supargiyono (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
Malaria is an infectious disease in tropical countries including Indonesia which causes serious clinical manifestations and even death. Indonesia Ministry of Health targets that malaria is eliminated from this country by 2030. In Java, malaria is targeted to be eliminated by 2015. However, elimination has not been achieved because some areas, including Kulon Progo, Daerah Istimewa Yogyakarta often experiences outbreaks (Kejadian Luar Biasa) in recent years. As microscopic diagnosis is a gold standard diagnosis for malaria, thus accurate microscopic examination is important. Disappearance of malaria cases in malaria pre-elimination areas causes laboratory workers/microscopists are less exposed to experience in identifying malaria. As part of quality assurance, continuous quality control is expected to maintain the accuracy of malaria diagnosis in endemic areas. However, the cross-check sistem as a part of this quality control strategy still has constraints, such as: transportation costs, limited human resources and irregularity. Ibm team of Faculty of Medicine UGM has successfully developed a digital microscopic cross-check sistem. This method is able to bridge the distance and time constraint also transportation costs of slide submissions to be cross-checked to the referral laboratory. Our study partners were microscopists of Kulon Progo Primary Health Centers (Puskesmas) facilitated with digital devices installed in a microscope. Partners were trained to: 1. take microscopic images of suspected malaria parasites and 2. familiarize with digital cross-check sistem. The successful implementation of digital malaria cross-check is expected to improve the accuracy of malaria diagnosis and assist the Government in malaria elimination program especially in Kulon Progo. This system has been registered for Intellectual Property Right no. 091306 obtained from Department of Justice and Human Right of Republic of Indonesia.